A prospective closed loop audit on the quality of the operative notes in a general surgical unit in a quaternary care centre - Javid, Mohamed; Swaminathan, Shanthi Ponnandai; Jebasingh, Arun Victor; Velayutham, Manivannan; Mani, Rajeswari (International Surgery Journal, 2020)
Background: Proper documentation of the surgery done in the form of operative notes is a very important aspect of surgical practice. The aim of this clinical audit was to identify the existing standard of the operative notes written in a general surgical unit in a quaternary care hospital; and to compare it with the recommendations given by Royal College of Surgeons, England (in Good Surgical Practice, 2014) and if needed, to improve the standard of practice. Methods: In the first loop of this prospective audit, 75 consecutive operative notes which were written were compared with the RCS guidelines and the areas which had missing data were identified. These areas were informed to the residents, who are primarily involved in the documentation of the operative notes. The second loop of the audit was conducted after a gap of 4 months involving 75 consecutive operative notes again. Results: The areas which were initially deficient were better documented when analysed in the second loop. Conclusions: Documentation of operative notes does not always comply with the set guidelines as highlighted in the first loop of our audit. But by employing a clinical audit it is possible to identify the existing deficiencies and thereby improving the standards of practice. Also, operative note writing should be taught as part of surgical training. Definitions should be clearly provided, and specific guidelines should be established to improve the quality of the operative notes and their use to improve patient safety.